A new multifunctional DVR for compensation of voltage sag - Rao, N. Srinivasa; Priyadharson, A. Selwin Mich (International Journal of Engineering and Technology, 2018)
Today, power quality is considered as a significant application. i) Highly effectual variable speed drive, ii) sophisticated electronic equipment together with iii) power electronic controller, is utilized to enhance power quality (PQ). Voltage sags are the prevalent PQ disturbances on the distribution system. It occurs on account of the faults developed in the electrical network or by the working of a huge induction motor. It is resolved by utilizing the conventional power device termed DVR (Dynamic Voltage Restorer). It is of small size and also low cost. It proffers quick dynamic response to the disturbance. A multifunctional DVR is utilized here to augment the PQ with the aid of P+ Resonant and Posicast controllers to remove the steady-state error (SSE) and enhance the transient response. Simulation outcome displays that the DVR enables to restrain the emergency scenarios of the distribution systems. The prevailing limitation reinstate the PCC (i.e. point of common coupling) (i.e. the bus to which every feeders are linked) voltage and Defend the DVR itself. The DVR performs as virtual impedance with the chief target of shielding the PCC voltage all through the downstream fault without affecting real power injection in the DVR which is the significant innovation discussed here.